AN ANALYSIS OF MOTIVATION AND COMPENSATION ON LECTURERS JOB PERFORMANCE AT INFORMATICS AND BUSINESS ISTITUTE (IBI) DARMAJAYA - Besti Lilyana (Proceeding International Conference on Information Technology and Business, 2015)
The research is aimed at knowing the influence ofmotivation and compensation on lecturers jobperformance at Informatics and Business Institute (IBI)Darmajaya Bandar Lampung. The problems of theresearch are 1) Do motivation and compensation receivedby the lecturers of IBI Darmajaya have an effect on theirjob performance? 2) How far is the relationship betweenmotivation and compensation and job performance? 3)Which factor is more dominant between motivation andcompensation that affects the job performance?This research uses double linear regression analysismethod. The variables of the research are motivation andcompensation as independent variables and jobperformance as dependent variable. To know theinfluence of independent variable on dependent variable ispartially used ttest and to know the influence ofindependent variable on dependent variable used Ftest.This research is a population research or a census studywhere 51 respondents taken out of the whole number ofactive fulltimelecturers at IBI Darmajaya.The result of the research indicates that motivation andcompensation variable affects lecturers job performance,both simultaneously and partially. In addition, in theresult of the research it is found that motivation variable ismore dominant that compensation variable in affectinglecturers job performance.KEY WORDS :Motivation, Compensation, and JobPerformance